The Effect of Supervisor Support and Teamwork on Employee Performance Mediated by Job Satisfaction - Gilang Tri Amanda; Ekhsan, Muhamad (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2024)
The purpose of this study is to determine how teamwork and supervisor support impact employee performance and job satisfaction as a mediating variable. This study used quantitative methods, and SmartPLS 3 software was used to conduct Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. The sample consisted of 450 people selected from three electronic companies in the EJIP Cikarang area. The results of this study show that supervisor support and teamwork have an effect on employee performance, and job satisfaction also has an effect. In addition, this study shows that supervisor support and teamwork affect employee performance indirectly through the mediation of job satisfaction. This finding shows how important the role of job satisfaction is as a mediator between supervisor support and teamwork in employee performance. Managerial implications include the importance of improving the quality of supervision, building effective teamwork, and identifying factors that increase employee job satisfaction. Also discussed are the limitations of the study and suggestions for future research.